Wnt signaling as target for the treatment of osteoarthritis. Issue 5 (October 2017) - Stampella, Alessandra; Monteagudo, Silvia; Lories, Rik
Abstract: Osteoarthritis is a severe and common rheumatic and skeletal disease for which currently no specific drugs are available. The Wnt signaling pathway modulates key biological processes in development, growth, homeostasis, and disease, particularly in the joints and bone. Excessive activation of the Wnt signaling pathway in the articular cartilage has been clearly associated with the onset and severity of osteoarthritis. Hence, targeting Wnt signaling may be an excellent approach to develop specific drugs useful for the treatment of osteoarthritis. In this article, we review the biology of Wnt signaling in the context of osteoarthritis; we also analyze the gradual improvement of our molecular understanding of Wnts in the joint and oversee current progress toward the development of Wnt inhibition as therapy for osteoarthritis. At least one Wnt inhibitor is currently going forward in the clinical evaluation process, potentially marking the beginning of a new era in the management of osteoarthritis.